Perspektif Hukum Islam Terhadap Praktik Pemanfaatan Barang Gadai Berupa Rumah Di Desa Sragi Kecamatan Songgon Kabupaten Banyuwangi - Mustofa; Shinta Ayu Lestari; Misba Huddin (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2022)
Pegadaian is a formal financial institution tasked with channeling financing in the form of providing loans to the public based on Sharia principles called pawning (rahn) in Fiqh Muamalah. To get a loan, the community must surrender the valuable objects they have to the pawnshop as collateral for their debt. The community in general recognizes a pawn with one of the debt agreements with collateral, where Rahn's party must return the debt with a period determined by both parties, if Rahn cannot repay the debt then the collateral will become the property of the murtahin. Usually, among the people, the collateral is used until Rahn can redeem the pawned item back. Thus the focus of this research is to find out the perspective of Islamic law on the practice of pawning goods in the form of houses in Sragi Village, Songgon District, Banyuwangi Regency. To answer the focus of this research, the researcher uses a qualitative method based on a doctrinal approach and interpretation of the sources and data obtained. Based on the results of this study, it can be seen that the practice of using pawned goods that occurred in Sragi Village, Songgon District, Banyuwangi Regency, if the murtahin occupies or uses the pawned goods is allowed, as long as the murtahin has obtained permission from the rahin and of course it has all been agreed in the initial agreement.